Bait and switch or double-edged sword? The (sometimes) failed promises of calling. (January 2015) - Berkelaar, Brenda L; Buzzanell, Patrice M
How people talk about their work and careers matters. Desiring meaningful work, people increasingly describe work and careers as a calling. Such callings may be secular or sacred. Popular ways of talking about calling often create problematic, rather than positive, career and life outcomes. In this article, we examine five common, historically influenced assumptions underlying contemporary talk about secular and sacred callings: necessity; agency and control; inequality; temporal continuity; and neoliberal economics. We showcase some of the likely downsides of calling as these underlying assumptions interact with people's everyday lives. We suggest possible solutions for rehabilitating calling to help people find some of the career and quality-of-life benefits that calling promises. In sum, this essay contributes to a more nuanced understanding of calling and agency in contemporary careers while also offering a framework and direction for developing research and practice on calling.